Performance Test and Cause Analysis of Girth Weld with Defects. Issue 1 (1st October 2022) - Xu, Yan; Wu, Mingchang; Nie, Xianghui; Feng, Zhenjun; Li, Liang; Yang, Fengping
Abstract: In this study, the performance test and defect anatomy analysis were carried out for a girth weld of the pipeline. The results of the girth weld tensile test, groove hammer break test and Vickers hardness test showed no obvious abnormality, and the impact toughness and bending test results were not ideal. In the conventional inspection process, it was found that there were tiny unfused girth welds at 6 o 'clock and 9 o 'clock positions, and the maximum direction size of defects on the wall thickness section was 1.57 mm. The defects at the position from 6 o 'clock to 7 o 'clock found by on-site X-ray detection were identified as the existing non-fusion defects by anatomical analysis, and should be considered as the root of incomplete welding defects that could not be completely eliminated during repair welding. The length and height of the defects are 9 mm and 1.38 mm.